QUAL2E simulation of selected pollutant constituents for Semberong River, Batu Pahat, Johor - Kesot, Mohd Jahaya (2004)
A comparison between actual data collected on site and laboratory analyzed against simulated results using mathematical model represented by Enhanced Stream Water Quality Model (QUAL2E) computer programme for selected pollutant constituents for part of Sungai Semberong is proposed. Four types of stream pollutant constituents will be analyzed to represent the consistency of the compared results, Conventional pollutant, conservative constituent, reactive consituent and general water characteristic. Various reaction coefficients constant and global parameter associated with the selected constituents will be analyzed to determine the most suitable value for adoption to local condition. Successful verification of the consitency and and realiability of the simulated results will pennit adoption of the mathematical model and the computer programme for subsequent analysis of the stream water quality parameters for Semberong River.